Are sprint and distance freestyle swimmers technically different? - McCabe, C.; Sanders, R. (2009)
Competitive swimmers tend to specialise in either sprint or distance events to suit their innate and conditioned physiological characteristics. As a result, coaches design specific training programs to direct the swimmers` optimal performance in their chosen event. Despite the specialisation of the swimmer, these training programs often include a wide range of intensities in order to develop physiological aspects regarded as deficient (Lydersen, 1999; Johnson and Gadboy, 1999). However, the possible impact of this accepted practice on the swimmers` stroke mechanics has not been considered adequately. For example, it is unknown whether sprinters training at a distance pace, or vice versa, will adapt their technique to the extent that may negatively effect their performance. Bearing in mind the principle of specificity with regard to training, this is an important consideration.